Analisis Program Pembelajaran Berbasis Higher Order Thinking Skills di MI At-Taqwa GUPPI Wojowalur Daerah Istimewa Yogyakarta Tahun Ajaran 2018/2019 - Eka Yusnaldi; Fia Alifah Putri; Wahyu Iskandar (Institut Agama Islam Negeri (IAIN) Curup, 2021)
The rules 2013 Curriculum is very interested in providing learning processes and items that have Higher Order Thinking Skills (HOTS) degrees for students. The HOTS function is very representative of providing logical, reflective, critical, creative and metacognitive abilities which are higher order thinking abilities. This study aims to determine the HOTS-based learning planning program in MI At-Taqwa GUPPI Wojowalur Yogyakarta Special Region 2018/2019 and HOTS-based learning implementation program in MI At-Taqwa GUPPI Wojowalur Yogyakarta Special Region 2018/2019. Data were analyzed by describing or describing data according to the rules of descriptive qualitative research by taking interview and documentation data. In determining the subject, the researcher used a non-probability sample. The results of this study that (1) HOTS learning program 2018/2019 school year teachers implement learning plans using syllabus and RPP based on HOTS (2) HOTS learning implementation program 2018/2019 school year teachers have used variations in the determination of HOTS-based methods such as discussion, question and answer and students' ability to argue.